Strategi Pemasaran "COKUMA" Melalui Analisis SWOT - Sulaiman, Fahmi; Silalahi, Flora (Jurnal Masyarakat Indonesia (Jumas), 2023)
This study aims to find COKUMA's marketing strategy with the SWOT analysis method. This research is a content analysis research. The object of this research is the efficacy of mangosteen peel which is beneficial for health. Data was collected through interviews and documentation. Interviews were conducted to find our product marketing strategy with the SWOT analysis method used for students. The technique of checking the validity of the data uses the cross check technique. The results of this study indicate that COKUMA has its own marketing strategy through SWOT analysis so that we know the strengths, weaknesses, opportunities and threats in COKUMA's marketing strategy research.